Possibility of Resocialization in the Penitentiary System of Lithuania - Piliponytė, Jolanta (Sociologija. Mintis ir veiksmas, 2015)
The article aims to discuss the possibilities of resocialization in the Lithuanian penitentiary system. The discussion takes its point of departure in an overview of the statistical data of secondary crime rates. The author argues that the contradicting nature of the idea of resocialization is defined by the tension between the principles of the penitentiary system (control, submission and isolation) and the notion of the individual as self-expressive and freely choosing on which the penitentiary system is grounded. The author develops the discussion through by analyzing the data of a survey research on the one hand and the interviews with the experts of the penitentiary system on the other.
Keywords: resocialization; penitentiary system; facilities of detention; repeat crimes